A View on 20 Years of Antimicrobial Resistance in Japan by Two National Surveillance Systems: The National Epidemiological Surveillance of Infectious Diseases and Japan Nosocomial Infections Surveillance - Satowa Suzuki (MDPI AG, 2021)
The Ministry of Health, Labour and Welfare (MHLW) of Japan has conducted two national surveillance systems for approximately 20 years to monitor antimicrobial resistance (AMR) in bacteria: the National Epidemiological Surveillance of Infectious Diseases (NESID) and the Japan Nosocomial Infections Surveillance (JANIS). Data accumulated for 20 years by these two surveillance systems have helped depict the epidemiology of the representative AMR bacteria in Japan chronologically. The epidemiology of methicillin-resistant Staphylococcus aureus teaches us that once AMR bacteria have established their high endemicity, controlling such AMR bacteria requires time and is challenging. On the other hand, the epidemiology that multidrug-resistant Acinetobacter sp. exhibits when a strict containment policy for AMR bacteria was introduced in the early phase of its emergence and spread reveals that it is possible to control it. Detailed epidemiology provided by these two different national surveillance systems in Japan enabled us to set up the goal for controlling each AMR bacteria at the hospital level to the prefecture/national level. It is the public health authorities' responsibility to maintain a good surveillance system for AMR bacteria and share the data and findings with healthcare professionals and academicians.